Kiriku hingehoiutöö eriolukorra ajal - Soom, Kaido; Schihalejev, olga (Usuteaduslik Ajakiri, 2020)
Pastoral Counseling During the Period of Emergency The article analyses the impact of the coronavirus pandemic in Estonia on pastoral counseling offered by the clergy of the Estonian Council of Churches. Seventy-two respondents from different denominations answered the questionnaire. Despite state restrictions, pastoral counseling has continued and even intensified, being initiated by clergy and requested by the people in need. Traditional face-to-face meetings were replaced predominantly by telephone or electronic communication. Many other forms of work done in churches were moved online. The most common topics of pastoral counseling were related to the practical issues of daily life rather than to spiritual needs or existential questions. This result may be due to Estonia’s post-Christian milieu.